Primary and Secondary School Teachers' Workload and the Influencing Factors: Based on the Survey Data from the Primary and Secondary Schools in City G - LI Yuan; XIE Minmin; LIU Hui (Jiaoshi jiaoyu xuebao)
The level of supply of work resources can reflect the work status of employees to a certain extent.Through the data analysis of 24, 949 valid questionnaires of primary and secondary school teachers in city G, it was found that the working hours of primary and secondary school teachers far exceed the national mandatory requirements, and the workload is generally at a moderate level.Among various types of workloads, educational and teaching burden are relatively heavy. There are significant differences in the workload of primary and secondary school teachers under different conditions such as gender, education background, teaching experience, professional title level, and teaching stage.Both material resources and cognitive resources have predictive effects on teachers'workload.Based on this, the following suggestions are put forward for reducing the burden of teachers in big cities: establish a correct concept of teachers'workload; pay attention to the differences in teachers'workload under different conditions; coordinate the relationship between school management and education and teaching; and improve the professional quality and level of primary and secondary school teachers.